2015
DOI: 10.3174/ajnr.a4501
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI for Analysis of Active Multiple Sclerosis Lesions without Gadolinium-Based Contrast Agent

Abstract: BACKGROUND AND PURPOSE:Contrast-enhancing MS lesions are important markers of active inflammation in the diagnostic work-up of MS and in disease monitoring with MR imaging. Because intravenous contrast agents involve an expense and a potential risk of adverse events, it would be desirable to identify active lesions without using a contrast agent. The purpose of this study was to evaluate whether pre-contrast injection tissue-relaxation rates and proton density of MS lesions, by using a new quantitative MR imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 29 publications
6
51
1
1
Order By: Relevance
“…Therefore, alternative imaging strategies that accurately characterize MS disease activity without Gd should be actively investigated, established, and disseminated to the MS community. Previous efforts of identifying Gd-enhancing lesions have not been satisfactory, yielding a diagnostic accuracy of AUC=0.83 in ROC analysis using semi-quantitative and quantitative T1w and T2w imaging 10, 12 and an accuracy of 72.1% using diffusion weighted imaging 13 . Fundamentally, relaxation time and the diffusion coefficient are proportional to the correlation time, which reflects cellular contents in a voxel and cannot differentiate between Gd-enhancing and non-enhancing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative imaging strategies that accurately characterize MS disease activity without Gd should be actively investigated, established, and disseminated to the MS community. Previous efforts of identifying Gd-enhancing lesions have not been satisfactory, yielding a diagnostic accuracy of AUC=0.83 in ROC analysis using semi-quantitative and quantitative T1w and T2w imaging 10, 12 and an accuracy of 72.1% using diffusion weighted imaging 13 . Fundamentally, relaxation time and the diffusion coefficient are proportional to the correlation time, which reflects cellular contents in a voxel and cannot differentiate between Gd-enhancing and non-enhancing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the data in Fig.6 suggest that 1) T2w lesions with relative susceptibility value near zero may be nodular enhancing, opening another venue for the current exploration of identifying enhancing lesions without gadolinium injection 3335 , and 2) simultaneous QSM and R2* increase indicates iron accumulation in MS lesion, offering an in vivo tool to study iron-related inflammation behind a sealed BBB that cannot be demonstrated with conventional imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Given that blood-brain barrier disruption and edema formation are correlated phenomena, 28 a higher V EPW may suggest the existence of blood-brain barrier disruption. Although R1, R2, and PD are good predictors of lesion enhancement, 29 the combination of V MY and V EPW may be a better predictor because it provides a more specific description of a lesion. This conjecture was not validated here because almost all lesions investigated were chronic and no contrast medium was used.…”
Section: Discussionmentioning
confidence: 99%